2022
DOI: 10.1007/s10869-022-09834-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Red Tape and Precursors of Turnover: the Roles of Work Engagement and Career Adaptability

Abstract: Drawing on job demands-resources theory, we propose that perceived red tape, as a hindrance job demand, triggers attitudinal and behavioral precursors of turnover in employees (turnover intentions and job search behaviors) by reducing their work engagement. In addition, we hypothesize that career adaptability, as a personal resource, buffers the detrimental effects of perceived red tape. In Study 1, three-wave data collected from employees (N = 202) working in Tanzanian public sector organizations supports the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
3
2
0
Order By: Relevance
“…This finding also supports the research of Jiang et al (2022), who highlighted that employees who perceive higher levels of red tape are more prone to decreased work engagement. When employees encounter unnecessary or inefficient procedures that hinder their work progress, they often need help recognizing their work's significance and positive value, leading to a decline in engagement.…”
Section: Red Tape On Work Engagement and Employee Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…This finding also supports the research of Jiang et al (2022), who highlighted that employees who perceive higher levels of red tape are more prone to decreased work engagement. When employees encounter unnecessary or inefficient procedures that hinder their work progress, they often need help recognizing their work's significance and positive value, leading to a decline in engagement.…”
Section: Red Tape On Work Engagement and Employee Performancesupporting
confidence: 90%
“…Furthermore, when employees face ineffective or unnecessary procedures that hinder their progress at work, they often require assistance to identify their work's importance and positive aspects to sustain their motivation. Jiang et al (2022) state that employees who perceive a higher level of red tape are more likely to exhibit reduced levels of work engagement. In addition, Rauf (2020) also showed that the red tape can prevent the employees from completing their assigned tasks, reducing their commitment to their work.…”
Section: Red Tape As Job Demandmentioning
confidence: 99%
“…First, the significant direct effect of career adaptability to employee engagement. This finding corroborated preliminary study in various relationship between both constructs, i.e career adaptability as antecedent of engagement (Ghosh and Fouad, 2018;Yang et al, 2019;Daris, Anisah and Dewi, 2021), career adaptability as mediator of perceived-organization support and work engagement (Sunarjo et al, 2021), and career adaptability as moderator of red tape to work engagement (Jiang et al, 2023). Similar research by Arlina & Aprilianti (2019), which is conducted using civil servants of Indonesia as respondents, shows that the relation between career adaptability and career engagement is positive.…”
Section: Figure 2 the Structural Equation Modelling Calculationsupporting
confidence: 86%
“…This implies that personal resources, especially career adaptability, play a significant role in mitigating the impact of high-level job burnout on unfavorable work outcomes. Therefore, these findings build upon existing research and provide further evidence for the JD-R theory, which proposes that employees with ample resources tend to have more positive work experiences (Jiang et al, 2022;Bakker and Demerouti, 2007), greater self-evaluations, higher performance, and satisfaction (Skaalvik and Skaalvik, 2018), decreased burnout, and a lower likelihood of quitting their job (Xanthopoulou et al, 2007). In other words, educators who exhibit elevated career adaptability in the face of job burnout resulting from juggling teaching-research and work-family conflicts are more likely to actively pursue new opportunities, explore various research methodologies, and consistently enhance their skill set to revitalize their career trajectory.…”
Section: Moderation Mediating Effectsupporting
confidence: 72%
“…The findings of the present study support H3, indicating that career adaptability moderates the relationship between job burnout and adverse work-related outcomes, such as turnover intention, which is like Jiang et al's (2022) argument that career adaptability can moderate the harmful effects of significant career changes on perceptions of adapting effectiveness. Diverging from previous studies that have demonstrated the moderating role of career adaptability in the relationship between job demands and burnout in settings characterized by a single job demand, the present study focuses on concurrent multiple job demands, wherein career adaptability emerges as a moderating factor in the relationship between burnout and adverse job outcomes (Jiang et al, 2022). This implies that personal resources, especially career adaptability, play a significant role in mitigating the impact of high-level job burnout on unfavorable work outcomes.…”
Section: Moderation Mediating Effectmentioning
confidence: 97%